Pembelajaran dan hubungannya dengan pembelajaran arahan kendiri (self-directed learning) di kalangan pensyarah Universiti Teknologi Malaysia - Abdul Hamid, Mohd. Azahar; Mat Junoh, Adanan; Mohd. Balwi, Mohd. Koharuddin; Md. Shah, Ishak (Faculty of Management and Human Resource Development, 2004)

(untitled)
This is a survey research on academic staffs in Universiti Teknologi Malaysia (UTM) Skudai, Johor. The main purposes of this research are to identify the level of academicians’ understanding towards e-learning which has been implementing in UTM and their perceptions towards self-directed learning readiness. Besides that, this study is to identify the relationship between the level of understanding towards elearning and self-directed learning readiness, to identify the difference of self-directed learning readiness from the demographic aspects and to identify factors that influence the academicians to implement the e-learning. 216 academic staffs were selected as the research respondents and the data were gathered through distributed questionnaires. The data obtained were analyzed using descriptive and inferential statistics. The results showed that the level of understanding on the concept and responsibilities towards e-learning was high. Whereas, the level of understanding on the using of webpage, WebCT was intermediate. For self-directed learning readiness, most of respondents agreed that items provided as usually true of me and almost always true of me. Result from the correlation test indicates that there was a weak correlation between level of understanding and self-directed learning readiness (rs = 0.259) at significant level of 0.05. The data from survey also showed that education, posts and duration as an academic staff gave a significant differences in self-directed learning readiness. Generally, majority of respondents agreed that all the factors listed by the researcher have influences on the execution of e-learning except support from students and frequent course and training on ICT participation.